Penyelesaian Kewajiban Debitur Wafat Oleh Ahli Waris Pada Bank Syariah Indonesia KCP Jayapura Abepura - Nur Muhammad Huri; Husnul Yaqin; Moh Wahib; Faisal Faisal (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2023)
This paper describes the settlement of debtor obligations by heirs at Bank Syariah Indonesia KCP Jayapura Abepura. In the mechanism provided, there are three types of settlement: firstly, the bank submits a claim to the insurance guarantor; secondly, it is continued by the heirs when the guarantor's insurance is closed while the claim is not paid; thirdly, it is continued by the heirs when it is not stipulated in the agreement. According to the results of this study, there are two types of settlements. First, the settlement of the debtor's obligation by the heirs is by using the heir's assets (Article 175 paragraph (2) KHI) or using the assets belonging to the heirs and heirs (Articles 123 and 833 of the Civil Code). Second, the settlement of the obligations of the deceased debtor after being paid off by the insurer is carried out peacefully and does not harm the bank or heirs, with the insurance party being the guarantor according to the agreement and the heirs are not burdened with the obligations of the deceased debtor.